P STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA PADA PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 POLEWALI KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR: STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA PADA PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 POLEWALI KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Taupik. C; Abd. Wahid (Jurnal Ilmiah Tarbiyah Umat, 2024)
The problem studied in this research is what is the strategy of Islamic Religious Education teachers in instilling the values ​​of religious moderation in class VIII students at SMP Negeri 1 Polewali, Polewali District, Polewali Mandar Regency and what are the supporting and inhibiting factors for the strategies of Islamic Religious Education teachers in instilling Islamic Religious Education values? The value of religious moderation in class VIII students at SMP Negeri 1 Polewali, Polewali District, Polewali Mandar Regency. The type of research used is descriptive qualitative research. The data collection method is carried out by observation or observations and interviews based on facts in the field. The research results explained that the forms of religious moderation as per the results of interviews with class VIII PAI teachers at SMP Negeri 1 Polewali, Polewali District, Polewali Mandar Regency are saying hello, loving each other, a high sense of caring, working together and a high level of mutual respect and appreciation. Supporting factors are adequate facilities, the realization of cooperation between school members in religious activities and a school atmosphere that is quite conducive. The inhibiting factors are the level of ability, emotional maturity of students who are not the same, lack of non-Muslim religious educators, lack of facilities (learning media), limited time in learning and the absence of written school regulations that prohibit discrimination between religious adherents